2010
DOI: 10.1227/01.neu.0000377039.89725.f3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Prospective Long-term Radiographic Follow-up After Treatment of Single-Level Cervical Disk Disease With the Bryan Cervical Disc

Abstract: The device maintains preoperative motion at the index and adjacent levels, seems to protect against acceleration of adjacent-level degeneration as seen after anterior cervical discectomy and fusion, and remains securely anchored in the adjacent bone mass in the long run. Heterotopic ossification was frequently seen. The vast majority of all patients had a good to excellent clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…However, whether adjacent level degeneration is the result of the fusion, or simply the progression of the natural deterioration of the motion segments, is still a matter of controversy. Walraevens et al assessed the long term results (4–8 year) of disk replacement surgery with the Bryan Cervical Disc in 87 patients, and 4 patients (4.6%) of them underwent repeated surgery because of ASD, which is similar with our results [30]. Thus, ASD is considered to occur more frequently in patients with preoperative evident adjacent disc degeneration than those with preoperatively intact discs.…”
Section: Discussionsupporting
confidence: 84%
“…However, whether adjacent level degeneration is the result of the fusion, or simply the progression of the natural deterioration of the motion segments, is still a matter of controversy. Walraevens et al assessed the long term results (4–8 year) of disk replacement surgery with the Bryan Cervical Disc in 87 patients, and 4 patients (4.6%) of them underwent repeated surgery because of ASD, which is similar with our results [30]. Thus, ASD is considered to occur more frequently in patients with preoperative evident adjacent disc degeneration than those with preoperatively intact discs.…”
Section: Discussionsupporting
confidence: 84%
“…[22][23][24] One study with comparable follow-up reported a similar rate of HO. 25 While undesirable, HO does not appear to greatly impact clinical outcomes. 26,27 Considering that severe HO results in essentially a fusion, the clinical results may also be similar to ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…To date there have been several published reports of randomized controlled trials comparing ACDF with AD replacement with varying results. 4,21,35,48,64,70,71 The results of these trials have shown that AD replacement has excellent outcomes and in some instances is superior to ACDF with lower reoperation rates as well as improved clinical outcomes. Biomechanical studies are important to better understand neck function postsurgery and may provide insight into the mechanical factors that contribute to a good or poor clinical outcome.…”
mentioning
confidence: 99%